Social Protection in Contexts of Fragility and Forced Displacement: Introduction to a Special Issue. (13th December 2019) - Brück, Tilman; Cuesta, Jose; De Hoop, Jacobus; Gentilini, Ugo; Peterman, Amber
Abstract: Effective social protection is increasingly as essential to supporting affected populations in situations of protracted instability and displacement. Despite the growing use of social protection in these settings, there is comparatively little rigorous research on what works, for whom, and why. This special issue contributes by adding seven high-quality studies that raise substantially our understanding of the role of social protection in fragile contexts and in settings of forced displacement and migration. Together, these studies fill knowledge gaps, help support informed decision-making by policy-makers and practitioners, and demonstrate that impact evaluation and the analysis of social protection in challenging humanitarian settings are possible. The studies provide evidence that design choices in implementation, such as which population to target, choice of transfer modality or which messages are delivered with programmes, can make a substantial difference in the realisation of positive benefits among vulnerable populations. Furthermore, the findings of the studies underline the relevance of tailoring programme components to populations, which may benefit more or less from traditional programme implementation models.